Climate Change and Gender in Africa: A Review of Impact and Gender-Responsive Solutions - Awiti, Alex O. (Frontiers in Climate, 2022)
Climate change affects livelihoods and wellbeing. Women and men may experience the impacts of climate change differently. But climate change and its associated impacts affect women negatively. A review was done on peer-reviewed literature related to the impact of climate change on gender in Africa. While there is an abundance of credible scientific evidence on the impacts of climate change, there is a dearth of reliable dis-aggregated data and evidence on the impact of climate change on women. The review shows that climate change affects women more negatively compared to men in five impact areas: i) agricultural production; ii) food and nutrition security; iii) health; iv) water and energy; v) climate-related disaster, migration and conflict. The lack of gender dis-aggregated data undermines efforts to design gender-responsive interventions to enable women cope with and adapt to climate change impacts. While there is no consensus on what constitutes gender-responsive solutions to climate vulnerability and risk, the paper provides some priority action areas to stimulate debate and hopefully consensus for a starting point deeper engagement of women’s participation and motivating investments in creating frameworks for accountability for measurable gender-differentiated outcomes. efforts to design and deploy gender-responsive solutions to climate change impact must take a holistic, asset-based approach, which meaningfully seeks to identify dominant causal mechanisms and develops context policy and institutional options to address interlocking asset or capital dis-endowments.